2019
DOI: 10.1002/hed.25941
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and ultrasonographic features for predicting central lymph node metastasis in clinically node‐negative papillary thyroid carcinoma without capsule invasion

Abstract: Background To evaluate the association of preoperative clinical and sonographic features with central lymph node metastasis (CLNM) in patients with clinically node‐negative (cN0) papillary thyroid carcinoma (PTC) without capsule invasion. Methods Clinical and sonographic features of 635 cN0 PTC nodules without capsule invasion were retrospectively reviewed. CLNM was confirmed by pathology. Univariate and multivariate analyses were performed to analyze the predicting factors associated with CLNM in cN0 PTC with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
32
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 32 publications
5
32
1
Order By: Relevance
“…Preoperative neck US for cervical LNs plays an important role in deciding the extent of surgical resection, especially for determining the need for LN dissection. Unfortunately, the detection rate of cervical LN metastasis by US is unsatisfactory, especially for central neck LN metastasis (41). In our data, 113 tumors had LN metastasis, however, only 48.7% (55/113) of them were correctly reported as LN positive by US.…”
Section: Ln Metastasis Is One Of the Most Important Clinical Features Associated With Local Recurrence And Distant Metastasis (38)contrasting
confidence: 61%
“…Preoperative neck US for cervical LNs plays an important role in deciding the extent of surgical resection, especially for determining the need for LN dissection. Unfortunately, the detection rate of cervical LN metastasis by US is unsatisfactory, especially for central neck LN metastasis (41). In our data, 113 tumors had LN metastasis, however, only 48.7% (55/113) of them were correctly reported as LN positive by US.…”
Section: Ln Metastasis Is One Of the Most Important Clinical Features Associated With Local Recurrence And Distant Metastasis (38)contrasting
confidence: 61%
“…In the current study, age ≥55 years was a significant independent risk predictor of CLNM, which was consistent with the literature ( 38 ). The diameter was recognized as an independent risk factor for CLNM in patients with PTC ( 10 , 11 , 36 ), and our study got the same result. It may be attributed to the more extensive the tumors, the more aggressive and proliferative.…”
Section: Discussionsupporting
confidence: 80%
“…Zhan et al found that "taller than wide" shape and tumor size were independent risk factors for LNM (22). Besides, the presence of calcification, closer distance between tumor and capsule were also indicators for LNM (23). Although the previously-mentioned US characteristics are encouraging, diagnostic accuracy is greatly influenced by the expertise of the operator.…”
Section: Discussionmentioning
confidence: 99%